Design, construction and evaluation of a hand prosthesis based on soft robotics. - Ramos Niño, Orion Yari Santiago (Escuela Colombiana de Ingeniería, 2021)
With this study, it was possible to prove that single actuator devices can perform different types of gripping thanks to soft robotics. It was also shown that the PrHand3 device meets the basic requirements to be functional in activities of daily living. The next stage of this project will be to replicate the device and make aesthetic improvements to have a functional high-tech product for society.
Diseño, construcción y evaluación de una prótesis de mano basada en robótica blanda.
Keywords: Articulaciones artificiales; Manos robóticas; Compliant Mechanism; Dexterity Evaluation; Hand Prosthesis; Soft Robotics